PEMBELAJARAN ANSAMBEL MUSIK MELALUI PENDEKATAN APRESIASI DAN EKSPRESI DI SMPN 27 SEMARANG - pratama, yohanes hernawan (Jurnal Seni Musik, 2015)
The significance of art education is providing an aesthetic experience to students. SMPN 27 Semarang is a school that implements ensemble music lesson through appreciation and expression approach so that students gain aesthetic experience of art education, especially in the matter of music ensembles. The purpose of this study was to: (1) describe the ensemble music lesson through the appreciation approach in SMPN 27 Semarang, (2) describe the ensemble music lesson through expression approach in SMPN 27 Semarang. The location and target of selected research, researcher are SMPN 27 Semarang is located in East Ngesrep street VI No. 4 Srondol Bumi Indah village Sumurboto Banyumanik District of Semarang. This type of research is a qualitative descriptive study, which focused on the actual problems as such at the time of the research carried out. Data collection techniques used in this study are: observation, interview, and documentation. Criterion validity of qualitative data that the authors use in this study is the degree of confidence (credibility). In the results of this study are the material and the process of learning music ensemble through appreciation approach which students are encouraged to analyze musical ensemble performance by watching it together in the classroom and expression approaches which students are given the freedom of expression by playing simple arrangements songs Bagimu Negeri with an appreciation of each group in the class. The conclusions of this study were (1) the ensemble learning with a teacher appreciation approach refers to learning theory based on cognitivism, that learning can only occur when there is in the studied.The person's ability to learn, (2) through the teacher creation approach refers to the theories of learning according to the flow humanist, that each person determine their own behavior, student are free to choose according to their needs, not tied to the environment.